PENGARUH INFLASI, NILAI TUKAR DAN TINGKAT SUKU BUNGA TERHADAP HARGA SAHAM PADA SUB SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - Deni Permana; Adun Rahman; Ujang Hasan Mustopa (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2024)
The problems discussed in this research are 1) How are inflation, exchange rates, interest rates and share prices in the banking sub-sector listed on the Indonesian Stock Exchange. 2) What is the influence of inflation, exchange rates, interest rates partially on share prices in the banking sub-sector listed on the Indonesia Stock Exchange. 3) How is the influence of inflation, exchange rates and interest rates simultaneously on share prices in the banking sub-sector listed listed on the Indonesian Stock Exchange. The research results show that inflation financing, exchange rates, interest rates together have a significant positive effect on share prices in the banking sub-sector listed on the Indonesia Stock Exchange (BEI) for the 2008-2022 period.